ANALISIS GENRE PADA CERITA RAKYAT SULAWESI SELATAN: PENDEKATAN LINGUISTIK FUNGSIONAL SISTEMIK - Erin Bella Andini, - (2022)
Erin Bella Andini, 2002087. The Analysis of Genre on South Sulawesi Folklores: Systemic Functional Linguistics Approach This study aims to investigate the South Sulawesi Folklore Genre and identify specifically about a) the generic realization of folklore constructed in South Sulawesi, b) the lexicogrammatical features found in the folklore of South Sulawesi in constructing the stages of the story, and c) the lexicon that reveals as the characteristic of cultural identity of South Sulawesi. The main data researcher is in the form of folklore texts of South Sulawesi and obtained from the Ministry of Education and Culture. The results of the study indicate that the South Sulawesi folklore has six stages that form a potential generic structure (GSP). Based on the lexicogrammatical features, all stages are dominated by material processes because they are dominated by actions and actions in everyday life. Cultural influences are realized in the South Sulawesi folklore genre in the form of lexicon analysis. The finding of the lexicon is the word 'Puang' found in the folklore "Batu Memmana'e" and "Bale Masapie ri Bejo". Then, the lexicon 'Bajoa' and 'We Cudai' contained in the folklore "Assalenua Naengka Bajo". Based on the findings and data analysis, it can be concluded that South Sulawesi folklore is a genre that has the potential to be developed with a generic structure and lexicogrammatical features and follows the tastes of today's youth.